2011
DOI: 10.1029/2010wr009429
|View full text |Cite
|
Sign up to set email alerts
|

Persistence in intra‐annual snow depth distribution: 2. Fractal analysis of snow depth development

Abstract: [1] We present an analysis of high resolution laser scanning data of snow depths of three different slopes in the Wannengrat catchment (introduced in part 1) using omnidirectional and directional variograms for three specific terrain features; cross-loaded slopes, lee slopes, and windward slopes. A break in scaling behavior was observed in all subareas, which can be seen as the roughness scale of bare earth terrain which is modified by the snow cover. In the wind-protected lee slope a different scaling behavi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
62
6

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(90 citation statements)
references
References 31 publications
22
62
6
Order By: Relevance
“…6). The typical snow depth distribution is discussed in detail by Schirmer et al (2010b) and Schirmer and Lehning (2010). The Bowl is characterized by homogeneous lee-slope loading, with somewhat enhanced snow deposition in narrow channels.…”
Section: Snow Deposition Patternsmentioning
confidence: 99%
“…6). The typical snow depth distribution is discussed in detail by Schirmer et al (2010b) and Schirmer and Lehning (2010). The Bowl is characterized by homogeneous lee-slope loading, with somewhat enhanced snow deposition in narrow channels.…”
Section: Snow Deposition Patternsmentioning
confidence: 99%
“…This approach is sensitive to potential variations in the accumulation pattern that are driven by interaction of precipitation, wind, and topography (Deems et al, 2008;Schirmer and Lehning, 2011;van Pelt et al, 2014). For Findelengletscher, the data basis does not allow for a full assessment of the uncertainties introduced by this simplification.…”
Section: The Benefits Of Extensive Snow Accumulation Measurementsmentioning
confidence: 99%
“…The required spatial resolution is dependent on the application. It has been shown that changes in the dominating processes typically occur in the range of tens of meters [25] and at fine scale resolution (<5 m), surface roughness (features such as rocks and bushes) dominate the snow distribution [26], especially for small snow amounts. In order to simulate such fine (point-scale) resolution spatial variability, numerical models require grid resolutions of a few meters [21,27].…”
Section: Required Accuracy Of Measurementsmentioning
confidence: 99%
“…These two parameters are particularly important in alpine and sub-alpine regions, where snow is often around its melting point and temperature gradients within the snowpack may be large. These parameters also change on a spatial scale of tens of meters [25] and throughout the snowpack respectively, as well as temporally [76,78,79] on a scale of hours. As HS and HNS are calculated from SWE, these are also affected by the constant assumptions.…”
Section: Passive Microwave Sensingmentioning
confidence: 99%
See 1 more Smart Citation